A Transgenic Mouse Model of Eccentric Left Ventricular Hypertrophy With Preserved Ejection Fraction Exhibits Alterations in the Autophagy-Lysosomal Pathway - Wenzel, Kristin; Krämer, Elisabeth; Geertz, Birgit; Carrier, Lucie; Felix, Stephan B.; Könemann, Stephanie; Schlossarek, Saskia (Frontiers in Physiology, 2021)
The ubiquitin-proteasome system (UPS) and the autophagy-lysosomal pathway (ALP) are the main proteolytic systems involved in cellular homeostasis. Since cardiomyocytes, as terminally differentiated cells, lack the ability to share damaged proteins with their daughter cells, they are especially reliant on these protein degradation systems for their proper function. Alterations of the UPS and ALP have been reported in a wide range of cardiac diseases, including cardiomyopathies. In this study, we determined whether the UPS and ALP are altered in a mouse model of left ventricular hypertrophy and dilation expressing both cyclin T1 and Gαq under the control of the cardiac-specific -myosin heavy chain promoter (double transgenic; DTG). Compared to wild-type (WT) littermates, DTG mice showed higher end-diastolic left ventricular wall thicknesses and diameter with preserved ejection fraction. The cardiomyopathic phenotype was further confirmed by an upregulation of the fetal gene program and genes associated with fibrosis as well as a downregulation of genes involved in Ca2+ handling. Likewise, higher NT-proBNP levels were detected in DTG mice. Elevated steady-state levels of polyubiquitinated proteins and a reduced chymotrypsin-like activity suggested an impairment of the UPS in DTG mice. Evaluation of ALP key marker revealed a mixed pattern with higher protein levels of microtubule-associated protein 1 light chain 3 beta (LC3)-I and lysosomal-associated membrane protein-2, lower protein levels of beclin-1 and unchanged protein levels of p62/SQSTM1 in DTG mice when compared to WT. At transcriptional level, a >1.2-fold expression was observed for Erbb2, Hdac6, Lamp2, Nrg1 and Sqstm1, while a <0.8-fold expression was revealed for Fyco1 in DTG mice. The results related to the ALP suggested overall a repression of the ALP during the initiation process, but an induction of the ALP at the level of autophagosome-lysosome fusion and the delivery of ubiquitinated cargo to the ALP for degradation.